The influence of shrinkage-reducing agent solution properties on shrinkage of cementitious composite using grey correlation analysis. (20th December 2020) - Xiaonan, Wang; Wencui, Yang; Yong, Ge; Decheng, Feng
Highlights: Both deionized water and supernatant of cement slurry were used as the solvent. The change in pore size distribution and pore shape was found. The correlation degree of SRA solutions and pore structure with shrinkage was quantitatively analyzed. Abstract: Various shrinkage reducing agents (SRAs) are commercially available and can be used to reduce shrinkage risk in cementitious materials. It is well acknowledged that SRAs could lower autogenous shrinkage and drying shrinkage by reducing the surface tension. However, in the previous research of SRA, there are also some other influencing factors that have positive impacts on shrinkage inhibition. In this paper, the properties of solutions to which SRAs were added (i.e., the deionized water and the supernatant of cement slurry) were investigated, including the surface tension, contact angle, and viscosity. The total pore volume and pore size distribution of cement paste were measured using mercury intrusion porosimetry and nitrogen adsorption and desorption isotherms tests. Based on the capillary tension theory, the relevance of the above influencing factors to shrinkage properties of cement mortar was quantitative characterized by grey correlation analysis. The results demonstrated that the ranking of the correlation degrees: surface tension > the volume of the pore sizes in 10 50 nm > contact angle. These results can provide an extended understanding of the mechanism of SRA.